What Counts as a Proverb? The Case of NTC’s Dictionary of Proverbs and Clichés - Akbarian, Is’haaq (Lexikos)
A dictionary on proverbs should meet its claim in compiling the specific, relevant formulaic entries in order to retrieve the required information as quickly and as successfully as possible. The inconsistency between what such a dictionary claims to include and what it actually includes might stem from not attending to the possible boundaries between the fixed expressions that might as well be considered as guidelines in lexicography. Based on the distinctions between the fixed expressions offered in Gramley and Pätzold (1992) and Simpson (1985), NTC’s Dictionary of Proverbs and Clichés (Bertram 1996) was investigated as a sample proverb dictionary available, especially useful for non-native speakers. It was found that (a) the above dictionary failed to distinguish between proverbs and other prefabricated expressions and (b) nearly 67 percent out of the total number of the entries in the dictionary were found to be proverbs whereas around 33 percent of them turned out to be non-proverb items. Some lexicographic as well as research implications are also discussed at the end.